Evaluation of the Performance of Cooling Boxes with Variations of NaCl KCl and Tapioca Flour Solutions in Water as Energy Storage Media - Sukma, Aja Nadia; Setiawan, Adi; Taufiq; Jumadi; Andriani, Riza (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to determine which solution between NaCl, KCL, and tapioca starch shows the best performance in the charging and discharging process and to determine which solution is optimal between NaCl, KCL, and tapioca starch in maintaining the temperature longer. This study uses an experimental method, each material is tested using 10% solution through the process of releasing heat energy charging and absorbing heat energy discharging. The solution is frozen for 12 hours in a PCM bottle, then tested in a refrigerated box for 12 hours, with temperature monitored at several points. Data collection uses test techniques to see temperature changes in the charging and disharging testing process in the cooling box. Data analysis uses descriptive statistical analysis, which is carried out in the form of tables, images, graphs, and data presentations. The results showed that in the charging process NaCl experienced the fastest temperature drop reaching -16°C, NaCl also experienced a stable temperature increase of up to 11°C between KCl and tapioca flour. Meanwhile, in the discharging process, KCl is slower in decreasing the temperature to -11.8°C and experiencing a faster temperature increase to 24.2°C. The optimal solution of NaCl, KCl, and tapioca flour in maintaining a longer temperature is, tapioca flour is better because it can maintain a more stable and durable temperature than KCl and NaCl.